Factors Associated with Gestational Diabetes Mellitus and Its Outcome in Pregnancy - Amna Najam, Safia, Mahwash Jamil, Shamim Akhtar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Gestational diabetes mellitus is prevailing among pregnant females and affects the pregnancy outcome both in neonate and mother. As Pakistan is having high incidence of diabetes mellitus so females are at high risk of developing gestational diabetes mellitus (GDM). Other factors that may lead to GDM include age of female, weight, family history, previous history or family history of diabetes, stillbirths, previous history of large gestation and other socio-demographic factors. Whatever the risk factors are, the outcome of pregnancy in females with gestational diabetes is related to increased cesarean section, hyperglycemia and hypertension in mothers. Hypoglycemia is just after birth, macrosomia and large gestation in neonates. In order to determine risk factors and association of GDM with pregnancy outcome we have conducted this study with future implications for better pregnancy outcome. Methodology: An analytical study was conducted at the department of Gynae & Obs in public and private sectors hospitals of Rawalpindi and Islamabad Pakistan, over a period of 1 year and 9 months starting from July 2019 to March 2021. All the pregnant females diagnosed with gestational diabetes during their checkup in hospital visits were included in study through convenient sampling. The socio-demographic and laboratory data was obtained from their file record and pregnancy outcome was observed at the time of delivery in the same hospital. The analysis was done for 150 females by using SPSS version 26. Continuous variables were analyzed by mean and standard deviation while categorical variables were determined by frequencies in percentage. Outcome of pregnancy was analyzed by macrosomia, hypoglycemia in neonates and cesarean, hypertension in mothers. The association was determined between GDM and pregnancy outcome by chi-square test of significance where p <0.05. Results: In our study 150 females were of mean age 33.91 with ±3.72 SD. The mean self-reported, pre-pregnancy BMI(Kg/m2) of all pregnant females was 29.89 with ±4.55 SD. The mean number of children born to females was 3.4. There is no significant association of gestational period with neonatal or maternal death p- value was 0.308 and 0.410 respectively by applying chisquare test (p<0.05). The gestational diabetes mellitus is associated with cesarean section as 78(52%) females underwent elective c-section. Among these females 84(56%) developed hypertension and 18(21%) were managed for eclampsia. Neonates born with macrosomia were 48 (32%) and with hypoglycemia just after birth were 89 (59.3%). Keywords: Gestational diabetes mellitus (GDM), Outcome of pregnancy, Macrosomia, Neonatal hypoglycemia, Maternal hypertension.